Development of 2′-substituted (2S,1′R,2′S)-2-(carboxycyclopropyl)glycine analogues as potent N-methyl-d-aspartic acid receptor agonists - Risgaard, Rune (2013)
A series of 2′-substituted analogues of the selective NMDA receptor ligand (2S,1′R,2′S)-2-(carboxycyclopropyl)glycine ((S)-CCG-IV) have been designed, synthesized and pharmacologically characterized. The design was based on a docking study hypothesizing that substituents in the 2′-position would protrude into a region where differences among the NMDA receptor GluN2 subunits exist. Various synthetic routes were explored, and two different routes provided a series of alkyl-substituted analogues. Pharmacological characterization revealed that these compounds are NMDA receptor agonists and that potency decreases with increasing size of the alkyl groups. Variations in agonist activity are observed at the different recombinant NMDA receptor subtypes. This study demonstrates that it is possible to introduce substituents in the 2′-position of (S)-CCG-IV while maintaining agonist activity and that variation among NMDA receptor subtypes may be achieved by probing this region of the receptor.